PERSEPSI MASYARAKAT MELAYU PETALANGAN TERHADAP KEARIFAN LOKAL TANAMAN KARET DI DUSUN MADANG KECAMATAN PANGKALAN LESUNG KABUPATEN PELALAWAN - Wahyu Dicky; Eri Sayamar; Kausar Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research are: 1) Identify the types of local wisdom rubber trees that was, and is still applied in the rubber cultivation by the Malay community in the hamlet Petalangan Madang District of Pangkalan Lesung Pelalawan. 2) Determine the public perception of the indigenous Malay Petalangan rubber plant in Hamlet Madang District of Pangkalan Lesung Pelalawan. 3) Knowing the level of interest and the level of local wisdom strength rubber plant in people's lives in the hamlet Madang District of Pangkalan Lesung Pelalawan. This research was conducted in the hamlet Madang District of Pangkalan Lesung Pelalawan. Samples taken as many as 23 people, the sampling method, Snowball Sampling and Random Sampling. Data were collected through interviews and documentation. The analytical method used in this research is qualitative descriptive analysis, Likert scale and the Cartesian diagram. The results of this study are, 1) local wisdom rubber plant in the cultivation of rubber by the Malay community in the hamlet Petalangan Madang there are as many as 24 local wisdom. 2) the public perception of the indigenous Malay Petalangan rubber plants categorized agree. 3) the level of interest and the level of local wisdom strength rubber plant in the lives of people in the hamlet Madang there are two local wisdom in quadrant I, 21 Local wisdom in quadrant II, one local wisdom in quadrant III, and 2 Local knowledge in quadrant IV. Keywords: Community, Local wisdom, Rubber plant